Elaboration of damage maps for comparative analysis of the conservation status of the Santa Isabel Bridge in the years 2021 and 2022 - Gonzaga, Camila Marques do Rêgo; Vasconcelos, Felipe Duan Moura; Silva, Marcelo Avelino da; Monteiro, Eliana Cristina Barreto; Silva, Simone Rosa da (Technical and Scientific Journal Green Cities, 2024)
The city of Recife has numerous bridges that have existed for several years and are essential for the proper functioning of society. Over time, these special works of art suffer from the action of external weather and, in some cases, the action of man, which ends up generating countless pathological manifestations that require correction. As a result, this research’s main objective is to carry out a comparative study of the levels of degradation of the Santa Isabel Bridge between the years 2021 and 2022, aiming to collaborate with future restoration works at the site and also, with the increase in the number of research aimed at for the topic studied. Therefore, the case study was chosen as the methodological basis, being divided into four stages: selection of the object of study, carrying out two photographic inspections of the selected bridge (one in 2021 and the other in 2022), preparation of the Identification Sheets of Data (ISD) and damage maps, and execution of a comparative analysis of the bridge’s situation during the studied period. As a result, several pathological manifestations were found on the facades and in the central section of the bridge and, from the preparation of damage maps, it was possible to identify the areas that required more urgent repairs due to the high degree of incidence of anomalies. Based on the results, it was possible to show the importance of conserving this type of structure, as it is an important instrument for the economic, social, and environmental development of cities.